SAT0345 Patient Perceptions, Attitudes and Concerns about Anti-TNF Drugs. (10th June 2014) - Saygin, C.; Uzunaslan, D.; Hatemi, G.; Hamuryudan, V.
Abstract : Background: Patients' perceptions about the side effects of drugs can have major impact on compliance to treatment. This becomes especially important with newer therapies. Objectives: To evaluate the frequency of patient concerns about drug-related side effects among anti-TNF users and to delineate the factors predicting an increase in concerns aboutanti-TNF drugs. Methods: Rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA)patients who were using TNF-alpha antagonists and who attended our outpatient clinic for their routine visits were included. We questioned whether the subjects were satisfied with their drugs (rated from 0 to 3), concerned with the side effects at the beginning of treatment and at present (rated from 0 to 3), and if concerned, we asked them to specify the particular side effects that they had concerns on. In addition, disease activity in the preceding one week was assessed with "Rapid Assessment of Patient Index Data" (RAPID3). Perceptions and attitudes towards the drugs were assessed with "Beliefs about Medicines Questionnaire" (BMQ). Data regarding demographic features, disease duration, duration of drug therapy, and side effects that had been experienced during follow-up were collected from patient records.Having a score of ≥2 points in drug satisfaction or concern were tabulated as the presence of satisfaction or concern. Multivariate linear regression analysis was used to determine the factors associated with increased concerns about anti-TNF drugs. Results: We surveyed 100 patients (75 with AS, 21 with RA, 4 with PsA) who were currently using anti-TNF drugs (56infliximab; 26etanercept; 13adalimumab; and 5 golimumab). Demographic and clinical features as well as the number of patients with at least 2 points of concern scores, RAPID3 and BMQ scores are given in the table. Ninety percent of patients reported that they were satisfied with their anti-TNF medication.The most commonly feared side effects were neoplasms (52%), tuberculosis (42%), and damage to liver and kidneys (32%). Univariate analysis revealed that having AS was associated with a lower rate of concerns (p=0.006, β=0.278, 95%CI=0.072-0.408) and having concerns at the beginning of anti-TNF treatment was associated with higher rate of concerns at the time of interview (p=0.001, β=0.335, 95%CI=0.124-0.490). The presence of concerns at the onset of treatment predicted higher concern scores at the time of interview in multiple regression (p=0.01, β=0.279, 95%CI=0.064-0.458). Conclusions: Around one half of our patients reported that they were concerned about drug related adverse events at the initiation of anti-TNF drugs and this continued in one third after a mean duration of 44.19 months of treatment. The risk of cancer and tuberculosis were two major side effects that the patients were most concerned. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4131